Endothelial exosomes work as a functional mediator to activate macrophages - Lin, Wenwen; Huang, Feng; Yuan, Yin; Li, Qiaowei; Lin, Zhong; Zhu, Wenqing; Lin, Binbin; Zhu, Pengli (Frontiers in Immunology, 2023)
Introduction Intercellular communication is essential for almost all physiological and pathological processes. Endothelial cell (EC)-derived exosomes, working as mediators for intercellular information exchange, are involved in the pathophysiological mechanisms of atherosclerosis. However, the effect of inflamed endothelial exosomes on the function of macrophages (Mϕ) is poorly defined. This study aims to unravel how exosomes derived from tumor necrosis factor-α (TNF-α)-stimulated ECs (exo-T) affect Mϕ in vitro. Methods and results Exosomes derived from untreated ECs (exo) and exo-T were identified by using TEM, NTA, and western blot, and we observed that PKH67-labeled exo/exo-T were taken up by Mϕ. Exposure to exo-T for 24 h not only skewed Mϕ to the M1 subtype and exacerbated lipid deposition, but also promoted Mϕ apoptosis, while it did not significantly affect Mϕ migration, as detected by RT-qPCR, Dil-ox-LDL uptake assay, flow cytometry, wound healing assay, and transwell assay, respectively. In addition, exo/exo-T-related microRNA-Seq revealed 104 significantly differentially expressed microRNAs (DE-miRNAs). The target genes of DE-miRNAs were mainly enriched functionally in metabolic pathways, MAPK signaling pathway, etc., as determined using Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses. We further demonstrated by immunoblotting that exo-T intervention improves the phosphorylation of MAPK/NF-κB-related proteins. Discussion and conclusion Collectively, this study reveals that inflamed endothelial exosomes (TNF-α-stimulated EC-derived exosomes) work as a functional mediator to affect Mϕ function and may activate Mϕ through MAPK/NF-κB signaling pathways.